Fatigue induced changes in conical implant–abutment connections. Issue 11 (November 2015) - Blum, Kai; Wiest, Wolfram; Fella, Christian; Balles, Andreas; Dittmann, Jonas; Rack, Alexander; Maier, Dominik; Thomann, Ralf; Spies, Benedikt Christopher; Kohal, Ralf Joachim; Zabler, Simon; Nelson, Katja
Highlights Synchrotron Radiation. Visualization of micromotion in implant–abutment connection.